Exploring Metamodernism in Apartheid Literature : Case Study: The Promise (2021) by Damon Galgut - ZIDI, Elkhalil Mohammed; Nouioua, Amira Wafa (Faculty of Letters and Foreign Languages Department of English, 2023)
Many researchers, such as Linda Hutcheon, have reported a noticeable change in many aspects of contemporary art, architecture, and literature that goes beyond the deconstruction and irony of postmodernism. The term Metamodernism was suggested to theorize this post-postmodern phenomenon. In this light, this dissertation aims to explore this metamodernist trend in apartheid literature, more particularly, in Damon Galgut’s The Promise (2021) as a case study. To achieve this goal, it takes a qualitative approach in which descriptive analytical methods are used in order to analyse the themes and the stylistic techniques of the novel. This study concludes that the themes of the novel, such as death, history and morality as well as the stylistic techniques, such as post-irony, multiple narrators and intertextuality, demonstrate the return to some modern traditions, like that of authenticity and engagement, however without the total demise of postmodern scepticism. This resonates with metamodernism that is characterised by an oscillation between optimism and sincerity of modernism and scepticism and irony of postmodernism. Thus, this novel includes both of modern and postmodern features, and surpasses both of them.